Association Between Diabetic Dyslipidemia and Vascular Tissue Damage: A Biochemical and Histopathological Evaluation - Tariq Hussain, Qamar Yasmeen, Gul E Nasreen, Ikram Ul Haq, Sohaib Farooq, M. Shakil Zari Khawri Siddiqui, Maha Abdullatif, Fahmida Khatoon (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Type 2 diabetes mellitus is a major contributor to cardiovascular complications in diabetic dyslipidemia. However, there is no available data within Pakistan relating lipid abnormalities to actual histopathological vascular damage. Objective: To evaluate the correlation between biochemical lipid profile disturbance with the vascular histopathological change in type 2 diabetes mellitus patients. Methods: This cross-sectional study was conducted on 70 patients (50 diabetics, 20 non diabetic controls) who were patients of Elective vascular surgery in the Bakhtawar Amin Memorial Hospital, Multan & Sahara Medical College, Narowal from June 2022 to June 2023. Biochemically, fasting lipid profiles and HbA1c were assessed. H&E and Elastic Van Gieson staining were used to determine endothelial integrity, intimal-medial thickness, smooth muscle proliferation, and inflammatory infiltration in vascular tissues. Pearson correlation and multivariate regression were applied to the statistical analysis. Results: Levels of LDL-C, triglycerides, total cholesterol, and HDL-C were significantly higher in diabetics than in controls (p < 0.001). Histopathological findings in diabetics showed a greater rate of endothelial disruption (76%), intimal thickening (66%), and smooth muscle hyperplasia (58%). In multivariate regression, LDL-C and triglycerides were independently related to intimal thickness (p < 0.001), while HDL-C was inversely related (p < 0.01). The variance in the vascular wall changes was explained by the regression model by 61%. Conclusion: Histological evidence of vascular damage is strongly associated with diabetic dyslipidemia. In Pakistan, early lipid monitoring and management are crucial in preventing cardiovascular complications in type 2 diabetes, unless mandatory screening and timely treatment of lipid disorders are performed. Keywords: Diabetic dyslipidemia, LDL-C, intimal thickening, endothelial disruption, vascular histopathology, Pakistan